PENERAPAN MODEL PEMBELAJARAN QUANTUM TEACHING UNTUK MENINGKATKAN MOTIVASI BELAJAR IPAS SISWA KELAS V UPTD SD NEGERI 81 PAREPARE - Ali, Lukman; Muhammad Amran; Rizky Nur Amaliah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study is motivated by the low learning motivation of fifth-grade students at UPTD SD Negeri 81 Parepare. This classroom action research (CAR) aims to understand the process of implementing the Quantum Teaching model to improve learning motivation about the economic conditions in my region for fifth-grade students, and to assess the increase in learning motivation using the Quantum Teaching model. This study uses a qualitative approach. The subjects of this study are teachers and 14 fifth-grade students at UPTD SD Negeri 81 Parepare, consisting of 7 boys and 7 girls. The data analysis technique used is qualitative analysis. Based on the data obtained during the first cycle, teacher activity was in the "sufficient" qualification (C), student activity was in the "poor" qualification (K), and the motivation questionnaire results were in the "sufficient" qualification (C). In the second cycle, teacher activity remained in the "sufficient" qualification (C), student activity improved to the "sufficient" qualification (C), and the motivation questionnaire results were in the "good" qualification (B). In the third cycle, teacher and student activities were in the "good" qualification (B), and the motivation questionnaire results were in the "sufficient" qualification (B). The conclusion of this study is that implementing the Quantum Teaching model can improve the learning process and student motivation in the subject of economic conditions in my region for fifth-grade students at UPTD SD Negeri 81 Parepare.